1996
DOI: 10.1103/physrevlett.76.3196
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussian Transport Measurements and the Einstein Relation in Amorphous Silicon

Abstract: We propose an experimental procedure for testing the Einstein relation for carrier drift and diffusion in semiconductors exhibiting non-Gaussian or dispersive transport. We present corresponding hole time-of-flight and steady-state photocarrier grating measurements in hydrogenated amorphous silicon (a-Si:H). For a range of mobilities 10 25 10 22 cm 2 ͞V s we find that our estimates of hole diffusion are approximately twice as large as predicted by the Einstein relation and the mobility measurements. We conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 14 publications
2
105
0
1
Order By: Relevance
“…(9) Gu, et al [33] reported that this prediction agreed fairly well with measurements for a-Si:H, which is thus an experimental confirmation of the generalized Einstein relation.…”
Section: Appendix 2: Connecting the 7-parameter Model With Steady-stasupporting
confidence: 73%
See 1 more Smart Citation
“…(9) Gu, et al [33] reported that this prediction agreed fairly well with measurements for a-Si:H, which is thus an experimental confirmation of the generalized Einstein relation.…”
Section: Appendix 2: Connecting the 7-parameter Model With Steady-stasupporting
confidence: 73%
“…where F is the electric field; we have also used the detailed balance relation There is a "generalized Einstein relation" connecting this drift with diffusion of a carrier [33]; the root-mean-square width L D of an initially narrow distribution is related to L drift as:…”
Section: Appendix 2: Connecting the 7-parameter Model With Steady-stamentioning
confidence: 99%
“…Hexagon -"triode" a-Si:H (Ganguly, et al, 1996). Square -a-Si:H (Gu, et al, 1996). Triangle -aSi:H (Tiedje, et al, 1984).…”
Section: Relationship Of Ambipolar Diffusion Length Measurements and unclassified
“…1994 for details; the actual measurements are presented in Gu, Schiff, Grebner, Wang, and Schwarz, 1996). In particular we evaluate as D L h amb R = 2 2 / τ , where L amb is the ambipolar diffusion length actually measured by SSPG and τ R is the recombination response time measured from the photoconductivity decay time.…”
mentioning
confidence: 99%
See 1 more Smart Citation